KEANEKARAGAMAN JENIS LUMUT DI KEPULAUAN RAJA AMPAT, PAPUA BARAT - Windadri, Florentina Indah; Susan, Dewi (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2013)
Exploration and collection of mosses have been conducted in Raja Ampat islands (Waigeo, Batanta, and Salawati islands), The result recorded 85 collection numbers of mosses, consist of 56 species that belong to 25 genera and 11 families. Four species namely Calymperes palisotii, Ectropothecium monumentorum, Macromitrium orthostichum, Thuidium tamariscellum have status as new records to New Guinea and Taxithelium bakeri and Taxithelium oblongifolium are two new records to Indonesia .